The Darling Dahlias and the Eleven O'clock Lady - Albert, Susan Wittig (Albert, Susan Wittig. Darling Dahlias mysteries., 2015)
"The eleven o'clock lady has always been one of garden club president Liz Lacy's favorite spring wildflowers. The plant is so named because the white blossoms don't open until the sun shines directly on them and wakes them up. But another Eleven O'Clock Lady is never going to wake up again. Rona Jean Hancock--a telephone switchboard operator who earned her nickname because her shift ended at eleven, when her nightlife was just beginning--has been found strangled with her own silk stocking in a very unladylike position. Gossip sprouts like weeds in a small town, and Rona Jean's somewhat wild reputation is the topic of much speculation regarding who might have killed her. As the Darling Dahlias begin to sort through Rona Jean's private affairs, it appears there may be a connection to some skullduggery at the local Civilian Conservation Corps camp. Working at the camp, garden club vice president Ophelia Snow digs around to expose the truth...before a killer pulls up stakes and gets away with murder" --